A TRANSFER ENGINEERING TRAINING MODEL BASED ON THE STUDY OF BIOMECHANICS IN FUTSAL OR SMA/SMK STUDENTS IN BOYOLALI - Novaria Fajar Prasetya; Sugiyanto Sugiyanto; Sapta Kunta Purnama (Indonesia Sport Journal, 2022)
This study aims to produce a model of passing practice based on biomechanics studies in futsal ball games for high school / vocational students in Boyolali Regency. The research method used in this research is Research and Development (R&D). Sources of data in this study were researchers, coaches, athletes, futsal practitioners, multimedia experts, and biomechanics experts. The population comes from high school / vocational students in Boyolali Regency. The samples taken in this study were 6 samples for small group trials, 12 samples for large group trials, the group product effectiveness test with exercise media based on biomechanics studies used 10 samples, the group without exercise media based on biomechanics studies used 10 samples. Data collection techniques used in this study are qualitative and quantitative data collection. The instruments used in data collection were observation, interviews, questionnaires, and tests/tests. The types of data in this study are qualitative and quantitative data. The data analysis technique used in this research is qualitative and quantitative data analysis. The results of the research on the results of the effectiveness test obtained that the experimental group data was 33% - 48.0% and the control group was 16.0% - 43.0%. So based on these results, it can be concluded that the product of the passing technique training model based on the study of biomechanics in futsal for high school students in Boyolali is declared effective and feasible.Keywords: Media, Futsal, Beomechanics